1999
DOI: 10.1076/opep.6.4.229.4185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated ivermectin treatments on ocular onchocerciasis: evaluation after six to eight dosings

Abstract: In 26 villages (1987 population 12,302), hyperendemic for savanna onchocerciasis in North Cameroon, ivermectin was distributed annually between 1987/89 and 1995. Each year until 1992, ophthalmologic examinations were performed before treatment. A final examination was made in 1995. The effects of ivermectin on ocular onchocerciasis were assessed by following (a) the ophthalmologic indices in three cohorts of males recruited before treatment in 1987, 1988 and 1989, who were treated and examined annually, and (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…North Region, Cameroon, is part of a large area with a severe, blinding strain of onchocerciasis. 12 The presence of mf in the anterior chamber (5.5%) and in the cornea (3.6%) indicated that low rates of recent (acute) onchocercal eye disease were still present after years of ivermectin treatment. From the entomological side, previous studies have shown that ATPs above 100 were associated with a risk of onchocercal-associated eye lesions and blindness.…”
Section: Discussionmentioning
confidence: 99%
“…North Region, Cameroon, is part of a large area with a severe, blinding strain of onchocerciasis. 12 The presence of mf in the anterior chamber (5.5%) and in the cornea (3.6%) indicated that low rates of recent (acute) onchocercal eye disease were still present after years of ivermectin treatment. From the entomological side, previous studies have shown that ATPs above 100 were associated with a risk of onchocercal-associated eye lesions and blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite new chemotherapy protocols (30), filariae are still a major cause of serious tropical diseases (9,35); therefore, it is worthwhile to consider a vaccination approach as a complementary measure. We now have a particularly relevant experimental model at our disposal with the rodent filaria Litomosoides sigmodontis.…”
mentioning
confidence: 99%
“…The regression of punctate keratitis, early-stage iridocyclitis and chorioretinitis and to some extent scelorosing keratitis confirm ivermectin as an effective long term control means against ocular pathology in human O. volvulus infection [9], [10], [19], and the efficacy of annually repeated treatments extends to disease prevention, as it may halt migration of MF of O. volvulus into the eye and evolution of onchocerciasis-related ocular lesions. Previous studies accomplished in Africa have similarly observed that annual treatments for 2 to 8 years strongly reduced prevalence of ocular MF [10], [20], [21], [22], [23]. In the Americas, a complete reduction of disease of the anterior eye segment has been achieved with semi annual ivermectin dosing for 14 years [24], [25].…”
Section: Discussionmentioning
confidence: 92%
“…In the Americas, a complete reduction of disease of the anterior eye segment has been achieved with semi annual ivermectin dosing for 14 years [24], [25]. In African onchocerciasis cohorts, ivermectin therapy applied bi-annually or annually for up to eight years lessened the number of ocular MF and significantly improved anterior eye segment lesions, despite persisting skin MF [22], [23].…”
Section: Discussionmentioning
confidence: 99%